2000
DOI: 10.1074/jbc.275.6.4145
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating Hormone Inhibits All-trans-retinoic Acid-induced Retinoic Acid Receptor α Nuclear Localization and Transcriptional Activation in Mouse Sertoli Cell Lines

Abstract: The regulation of retinoic acid receptor alpha (RAR␣) signal transduction has not been well characterized. In this study, we determined whether all-trans-retinoic acid (tRA) and follicle-stimulating hormone (FSH) modulate RAR␣ receptor subcellular localization, leading to changes in its transcriptional activity and protein expression in mouse Sertoli cell lines. We found that tRA induced the nuclear localization of RAR␣ within 30 min and that longer term exposure increased the receptor transcriptional activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 36 publications
8
36
0
Order By: Relevance
“…However, some studies have demonstrated that RAR and TR are retained in the cytoplasm and move to the nucleus when ligands are supplied (13)(14)(15)(16). In particular, we also found that RAR␣ shuttles between the cytoplasm and the nucleus in the Sertoli cell line TM4 in response to AtRA (Fig.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…However, some studies have demonstrated that RAR and TR are retained in the cytoplasm and move to the nucleus when ligands are supplied (13)(14)(15)(16). In particular, we also found that RAR␣ shuttles between the cytoplasm and the nucleus in the Sertoli cell line TM4 in response to AtRA (Fig.…”
Section: Resultssupporting
confidence: 54%
“…6C), we can speculate on the function of CART1 in testis development. Although ligand-induced RAR cytoplasm-to-nucleus shuttling has been reported in testis Sertoli cells (15,16), little is known about the role of the putative cytoplasmic retention factor CART1 in testis. Recent data suggest that Rab11, another partner of CART1, is essential for fertility in the fruit fly (41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations